Nursing and Medical Students’ Perceptions of the Rehabilitation Medicine Course Unit: A Case Study of Mbarara University of Science and Technology. - Nabacwa, Lillian (Student's Journal of Health Research Africa, 2021)
Background: Physical and Rehabilitation Medicine is a medical specialty concerned with the improvement of functioning through diagnosis and treatment of health conditions, reduction of impairment, and preventing and treatment of complications. In an era of an increasing number of debilitating and disabling conditions arises the need for exposure of medical students to a goal of reducing the impact of disabling conditions and socially integrating the individuals suffering from the after-effects of these diseases. However, for the future development of this specialty, there is a need to explore students' attitudes and perceptions. Methodology: A qualitative descriptive design was employed in the study. The purposive sampling method was used to recruit 18 participants who had done the Rehabilitation Medicine course unit in the year 2019/2020. Data was collected using an interview guide. Data analysis was carried out using content analysis basing on existing themes. Results: Basing on already existent themes which included:- Resources for Rehabilitation Medicine, Activities are done during Rehabilitation Medicine Training, Support provided during Rehabilitation Medicine Training and Evaluation carried out during Rehabilitation Medicine, the study revealed students' report about the reading resources that were not well provided, appreciated the activities done during training and commended the lecturers for the optimum support rendered to them during training. They however expressed disagreement with the evaluation method of post-lecture tests as they reported they were conducted with bias and only targeted students that understand information firsthand from the lecture in class. Conclusion and recommendation: The study found out that students' perceptions towards rehabilitation Medicine are generally positive. Whereas the teaching resources were considered sufficient, access to reading materials is considered difficult.